2022
DOI: 10.1111/acfi.12917
|View full text |Cite
|
Sign up to set email alerts
|

What influences the implementation of IFRS for SMEs? The Brazilian case

Abstract: We investigate factors influencing the implementation of IFRS for SMEs in Brazil. Accountants and accounting firms from all over the country received a questionnaire about the perceptions of IFRS for SMEs. A logit regression on the factors associated with non‐implementation using 426 valid observations suggests that inconsistencies and incomprehensibility issues are the main factors preventing implementation. However, further investigation indicates that once participants know the standard, ‘implementation myt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Kaya and Koch (2015) suggested that developing economies, by deciding to adopt IFRS for SMEs, send a credible signal to lending institutions and international investors that they are willing to introduce an internationally acceptable set of high-quality financial statements. Despite little evidence of the benefits of implementing IFRS for SMEs and the fact that it could have significantly different implications in less developed economies, firms in these countries were mandated to implement it (Gonçalves et al, 2022).…”
Section: Ifrs For Smes In Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaya and Koch (2015) suggested that developing economies, by deciding to adopt IFRS for SMEs, send a credible signal to lending institutions and international investors that they are willing to introduce an internationally acceptable set of high-quality financial statements. Despite little evidence of the benefits of implementing IFRS for SMEs and the fact that it could have significantly different implications in less developed economies, firms in these countries were mandated to implement it (Gonçalves et al, 2022).…”
Section: Ifrs For Smes In Generalmentioning
confidence: 99%
“…The result of the Albu et al (2013) study showed that users of SMEs' financial statements in four developing countries, including Turkey, prefer a mandatory approach to the convergence approach in the implementation of IRES for SMEs. Indeed, as Gonçalves et al (2022) and De Moura et al ( 2020) stated, the incentive for SMEs to implement IFRS is less than that for listed companies; the reason refers to the fund resource, nature of oversight, and users.…”
Section: Benefit Of Ifrs For Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…The IFRS for SMEs is a simplified standard and is presumed to be easy to implement among accounting professionals. However, a study carried by Gonçalves, et al (2022), show that there are a lot of inconsistencies in application of the standard as a result of incomprehensibility issues in interpreting requirements of the standard, this calls for the IASB and regulators to come up with ways to make the standard more understandable. Norway is a case for a failed attempt to IFRS for SMEs adoption emanating from jurisdictional tensions and variations of local regulations and IFRS for SMEs requirements (Alon , et al, 2022).…”
Section: : Challenges Encountered In Different Regions During Adoptio...mentioning
confidence: 99%
“…SMEs and sizable corporations have different motivations for implementing standards. Larger corporations focus primarily on attracting investment, and therefore they use IFRS standards as a way of demonstrating to investors the quality of their equity (Gonçalves et al, 2022). Therefore, the adoption of IFRS for SMEs is often driven by different factors for SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%